The new serratus anterior plane block is more effective than the SPB block for early postoperative analgesia following modified radical mastectomy surgery - Gao, Ruizhen; Zhou, Gang; Zhu, Wanting; Zhang, Mingyu; Shu, Aihua; Zhou, Mi (Scientific reports, 2025)
Serratus anterior plane block (SPB) as a regional anesthesia technique is used for analgesia in modified radical mastectomy (MRM). The new serratus anterior plane (SAP) block is a novel approach that has been described recently. This study aimed to elucidate the effectiveness and safety of SAP block for pain management after MRM and compare the analgesic effects of SPB and SAP block with those of a control group during the postoperative period of MRM. In a prospective randomized controlled trial, sixty patients (n = 60) who underwent MRM surgery received either SPB or SAP block analgesia. The primary endpoint was the visual analog scale (VAS) score (at rest or with movement) at 2 h after MRM. The secondary outcomes were VAS scores at different time points (6, 12, 24 h) after MRM, stress hormone levels, and the consumption of opioid analgesics during the surgery. Sixty subjects were enrolled. The VAS scores with movement at 2 h postoperation were significantly lower in the SAP group than in the SPB group ( P = 0.027). The patients in the SAP and SPB groups had lower VAS scores compared with the Control group at 2 and 6 h after MRM, both at rest and with movement ( P < 0.001). The SPB and SAP blocks significantly reduced the consumption of opioid analgesics during surgery compared with the control group ( P < 0.001). This study revealed that both SPB and SAP blocks had good postoperative analgesic effects on modified radical mastectomy surgery, reduced the consumption of opioids, and decreased the stress response during surgery compared with the control group. Compared with SPB, the SAP block may have better analgesic effects during the early postoperative period of modified radical mastectomy surgery. Trial registration : This study was registered in the Chinese Clinical Trial Registry (Date of Registration: 08/08/2021, registration number: ChiCTR2100049692).